2020
DOI: 10.3390/cells9071630
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Changes in Cerebral Ischemia

Abstract: Cerebral ischemia is caused by perturbations in blood flow to the brain that trigger sequential and complex metabolic and cellular pathologies. This leads to brain tissue damage, including neuronal cell death and cerebral infarction, manifesting clinically as ischemic stroke, which is the cause of considerable morbidity and mortality worldwide. To analyze the underlying biological mechanisms and identify potential biomarkers of ischemic stroke, various in vitro and in vivo experimental models have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 129 publications
(210 reference statements)
1
67
1
3
Order By: Relevance
“…For example, although transcriptomics can reflect enormous genotypic changes, it has been shown to be insufficient for understanding the actual phenotype [ 32 , 33 ]. In contrast, in the case of metabolomics, which can constitute an endpoint feature of biological phenotypes [ 34 , 35 ], no amplification methods are available for very low-abundance metabolites, and quantitative analysis of the targeted method might likely provide only a partial representation of the overall metabolism [ 36 ]. Accordingly, a combination of transcriptomics and metabolomics, termed "metabotranscriptomics", has been utilised for a more comprehensive analysis of cells and evaluation of nanotoxicity following treatment with nanoparticles [ 4 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, although transcriptomics can reflect enormous genotypic changes, it has been shown to be insufficient for understanding the actual phenotype [ 32 , 33 ]. In contrast, in the case of metabolomics, which can constitute an endpoint feature of biological phenotypes [ 34 , 35 ], no amplification methods are available for very low-abundance metabolites, and quantitative analysis of the targeted method might likely provide only a partial representation of the overall metabolism [ 36 ]. Accordingly, a combination of transcriptomics and metabolomics, termed "metabotranscriptomics", has been utilised for a more comprehensive analysis of cells and evaluation of nanotoxicity following treatment with nanoparticles [ 4 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that miRNAs are critical modulators of CI-concerned cellular biological processes, including proliferation, apoptosis and so on. 19 Serum miR-124 may serve as a molecular marker for acute ischemic stroke. 20 Through the JNK signaling pathway, miR-145 accelerates the proliferation of endothelial progenitor cells in CI rats.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most leading causes of morbidity and mortality worldwide is cerebral ischemic disease, a common form of stroke. Cerebral ischemia is the fifth leading cause of death [ 75 ], and it is caused by the blockage of a blood vessel connected with a thrombus or embolus [ 76 ]. During brain ischemia, part of the brain lacks oxygen and nutrients, becoming damaged through induction of metabolic and cellular disturbances.…”
Section: Applications Of Metabolomics In Forensic Medicinementioning
confidence: 99%